THE EFFECT OF CORPORATE CULTURE, MANAGERIAL CAPABILITIES, AND DECISION MAKING ON LEADER PERFORMANCE IN MANAGING THE ENVIRONMENT - Ashar Pramono; Amos Neolaka; Rukaesih Achmad (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study was to determine the effect of corporate culture, managerial ability, and decision making on the performance of leaders in managing the environment. This research is a quantitative study. Survey data were analyzed by path analysis. The results showed as follows: (1) company culture has a positive direct effect on leadership performance (2) Managerial ability has a positive direct effect on leadership performance, (3) decision making has a positive direct effect on leadership performance, (4) corporate culture has positive direct influence on decision making, (5) managerial ability has a positive direct influence on decision making. Based on these findings, it can be concluded that any changes or variations that occur in the leader's performance have been influenced by company culture, managerial ability, and decision making.